The Effect of Servant and Transformational Leadership on Pastor Performance through Organizational Commitment - Nelson Kapitarau; Yohanis Rante; Ruben Tuhumena; Westim Ratang (Westscience Press, 2026)
This study analyzes the effect of servant leadership and transformational leadership on pastor performance, with organizational commitment as an intervening variable, in the Classis of GKI Port Numbai-Jayapura. The study employs a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through questionnaires administered to 257 elders and deacons from 19 sampled churches (out of 51 churches) and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. Qualitative data were obtained through in-depth interviews with 10 pastors and analyzed using grounded theory. The results show that servant leadership has no significant effect on organizational commitment (β = 0.046; p = 0.409) or on pastor performance directly (β = 0.074; p = 0.347). By contrast, transformational leadership has a positive and significant effect on organizational commitment (β = 0.814; p = 0.001) and pastor performance (β = 0.322; p = 0.003). Organizational commitment has a significant effect on pastor performance (β = 0.560; p = 0.000) and functions as a mediator. Mediation tests indicate that commitment fully mediates the servant leadership path (β = 0.237; p = 0.000) and partially mediates the transformational leadership path (β = 0.148; p = 0.002). The qualitative findings reinforce that effective church leadership integrates a serving disposition with transformational vision, yielding a conceptual model of Servant-Transformational Leadership for GKI Papua.